2022
DOI: 10.4314/wiojms.si2021.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Photo-physiology of healthy and bleached corals from the Mascarene Plateau

Abstract: This study presents the first report of variable photo-physiology of healthy-looking and bleached corals from the upper mesophotic waters of the Mascarene Plateau. In May 2018, during the FAO EAF-Nansen research expedition cruise, coral bleaching was visually observed. Five coral species from Saya de Malha Bank, namely Heliopora coerulea, Favites sp. and Porites sp. from 27 m and Acropora sp. and Lithophyllon repanda from 30 m, and three coral species from the Nazareth Bank, namely Acropora sp. and Galaxea fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…A study done during the 2010 bleaching event revealed differential recovery of different corals under variable bleaching conditions at Belle Mare, stating that there was no significant change in the PSII functioning of the pale colonies of Pocillopora damicornis and Galaxea fascicularis post-bleaching while bleached A. muricata had a higher Fv/Fm and a faster recovery than A. cytherea (Mattan-Moorgawa et al 2018). Differential coral bleaching and photo-physiological responses among corals are not restricted to around Mauritius only but have also been reported at the Saya de Malha, Mascarene Plateau, Indian Ocean (Bhagooli et al 2021b).…”
Section: Introductionmentioning
confidence: 84%
“…A study done during the 2010 bleaching event revealed differential recovery of different corals under variable bleaching conditions at Belle Mare, stating that there was no significant change in the PSII functioning of the pale colonies of Pocillopora damicornis and Galaxea fascicularis post-bleaching while bleached A. muricata had a higher Fv/Fm and a faster recovery than A. cytherea (Mattan-Moorgawa et al 2018). Differential coral bleaching and photo-physiological responses among corals are not restricted to around Mauritius only but have also been reported at the Saya de Malha, Mascarene Plateau, Indian Ocean (Bhagooli et al 2021b).…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, the urgency of in-depth studies on ascidian-related threats is even more pressing given that ascidian-induced-bioinvasion has been increasingly reported worldwide, especially following mass thermalinduced coral bleaching (Dijkstra et al 2007;Tebbett et al 2019). It is noteworthy that several local studies on photophysiological responses to thermal and other stressors have been conducted on scleractinian corals (Mattan-Moorgawa et al 2015Kaullysing et al 2016;Louis et al 2020;Bhagooli et al 2021b), seaweeds (Narain et al 2023;Bhagooli et al 2021c) and seagrasses (Bhagooli et al 2021c), microalgae (Sadally et al 2016;Soondur et al 2021Soondur et al , 2022 ascidians thermal stress responses are yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%